The effects of burnout on the professional activity of teachers - Călin, Mariana Floricica; Tasențe, Tănase; Seucea, Antonia (Technium Social Sciences Journal, 2022)
In recent years, burnout has been one of the most discussed mental health issues in modern societies. In a world facing major socioeconomic challenges, people face increasing pressure in their daily lives, especially at work. As a result, managers, employees and workers in a variety of industries and sectors around the world suffer from work-related stress, fatigue and burnout, the most prominent signs of which are often referred to as burnout syndrome. However, burnout is not exclusively work-related, as findings have shown that private life and social support also play a key role (Maslach & Jackson, 1984; Sprang, Clark, Whitt-Woosley, 2007). Professionals working in the public sector have also been found to be at greater risk of burnout than those in the private sector (Sprang, et al., 2007). Exposure factors such as long hours, assignment duration, caseloads, coupled with organizational factors such as lack of autonomy, low peer support, lack of training provide conditions where burnout will permeate inevitably at work in some capacity. The results will affect not only the professional but also the effectiveness of the job and the levels of care and support for the client (Boscarino, Figley, & Adams, 2004; Sprang, et al., 2007).